Analisis Penempatan Aparatur Sipil Negara pada Dinas Perikanan Kabupaten Lumajang - Nizma Yuraida (Majalah Ilmiah DIAN ILMU, 2022)
This study aims to determine the level of suitability of job specifications and the factors that influence the placement of State Civil Apparatus at the Fisheries Service of Lumajang Regency. This research uses descriptive qualitative method. This study explains the analysis of the distribution of employees who do not refer to the principle of placing the right person in the right position based on sources derived from scientific journals, books and official websites. The results showed that the placement of State Civil Apparatus at the Fisheries Service of Lumajang Regency using the theory proposed by Schuller and Jackson, namely knowledge, skills, abilities and personality were at a good level (appropriate) but not yet optimal, because of the influencing factors, namely leadership, human resources, regulations, and political positions.